Pengaruh Culture Shock Terhadap Kesehatan Mental Mahasiswa 2024 Di Yogyakarta - Habiballah; Muhamad fazrul baarii (GLOBAL SCIENTS PUBLISHER, 2025)
This study aims to analyze the impact of culture shock on the mental health of students in 2024 in Yogyakarta. As an educational city that attracts many students from various regions, Yogyakarta is a place where students often experience significant cultural shifts. Culture shock can trigger various mental health issues, such as stress, anxiety, and depression, which affect students' academic performance and quality of life. The research method employed is a quantitative survey involving new students as respondents. The results indicate that students experiencing culture shock tend to have lower mental health levels compared to those who successfully adapt to their new environment. Additionally, factors such as social support, involvement in cultural activities, and orientation programs play a crucial role in mitigating the negative effects of culture shock. This study recommends that educational institutions provide comprehensive orientation programs and psychological support services to help students adapt more effectively, thereby improving their mental health and academic performance.